2015
DOI: 10.1177/0363546514568089
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury in Major and Minor League Baseball Players

Abstract: Mild traumatic brain injury is an important problem in professional baseball players, especially for catchers. This study provides a foundation for future inquiry to reduce the incidence of MTBI in those positions at greatest risk and to provide a baseline as rules and equipment evolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 13 publications
(13 reference statements)
1
72
1
Order By: Relevance
“…During the first year of this electronic system, 161 concussions were recorded in the minor league and 29 in the major league, pointing to the need for improved concussion management. 18 MLB responded to this growing concern regarding concussions and the impact on player performance by implementing a standard concussion protocol at the start of the 2011-2012 season. 21,28,36,39 The protocol requires preseason neurocognitive baseline testing in the form of the SCAT5, use of the SCAT5 as a standardized concussion screening tool during play, the addition of a 7-day DL exclusively for concussed players, neurological evaluation demonstrating a return to baseline before returning to play, and prohibition of same-day return to play.…”
mentioning
confidence: 99%
“…During the first year of this electronic system, 161 concussions were recorded in the minor league and 29 in the major league, pointing to the need for improved concussion management. 18 MLB responded to this growing concern regarding concussions and the impact on player performance by implementing a standard concussion protocol at the start of the 2011-2012 season. 21,28,36,39 The protocol requires preseason neurocognitive baseline testing in the form of the SCAT5, use of the SCAT5 as a standardized concussion screening tool during play, the addition of a 7-day DL exclusively for concussed players, neurological evaluation demonstrating a return to baseline before returning to play, and prohibition of same-day return to play.…”
mentioning
confidence: 99%
“…14 The risk of traumatic brain injury is not new to the sport, with long-term outcomes increasingly investigated. 7 Although full-contact sports with repetitive neurotrauma have been linked to neurocognitive changes, the study of the short-term considerations after a player sustains SRC in limited-contact sports is also clinically relevant. 25 Performance and financial changes have relevance to individual players as well as franchises in strategic decision making regarding contract negotiations, trades, and acquisitions.…”
mentioning
confidence: 99%
“…Although a consistent definition of TBI was not found among the included studies, concussion was the most commonly identified outcome of interest (Table 3 ). Further, TBI rates varied according to sex ( 22 ), level of play ( 19 , 20 ) (high school, collegiate, major, and minor leagues) and whether it was a game or practice ( 18 , 28 ). The average injury rate (Table 4 ) per 1,000 athletic exposures (AE) was 0.13 (range 0.03–0.46) ( 20 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, TBI rates varied according to sex ( 22 ), level of play ( 19 , 20 ) (high school, collegiate, major, and minor leagues) and whether it was a game or practice ( 18 , 28 ). The average injury rate (Table 4 ) per 1,000 athletic exposures (AE) was 0.13 (range 0.03–0.46) ( 20 , 33 ). The most common mechanisms of injury (Table 5 ) included being struck (by a ball or bat) ( 17 ) and colliding with another player ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation